Dual‐energy contrast‐enhanced CT to evaluate scaphoid osteonecrosis with surgical correlation. Issue 1 (5th September 2018) - Pianta, Marcus; McCombe, David; Slavin, John; Hendry, Shona; Perera, Warren
Summary: To evaluate the validity of contrast enhanced dual energy CT using a lung perfusion algorithm in assessing for post‐traumatic scaphoid proximal pole avascular necrosis. From Aug 2013 to Aug 2016, 18 patients (19 wrists, 16 males, 2 females, mean age 28 years) were assessed as high‐risk for proximal pole scaphoid avascular necrosis by a single surgeon following a scaphoid fracture and were referred for contrast‐enhanced dual energy CT. 8 wrists had specimens sent for correlative histological analysis and 11 were correlated with operative notes. Eight surgical specimens were sent to histology and showed a 100% correlation (8/8) with the DECT findings. The remaining 11 wrists that did not have a specimen sent had in‐surgery findings that also correlated with DECT. A single case was discrepant (1/11) due to presence of an intra‐osseous ganglion, which was reported as osteonecrosis on CT, but considered viable at surgery. No case was called viable on CT that proved to be necrotic at either surgery or histologically. Contrast‐enhanced dual energy CT using a perfusion algorithm is an innovative and promising method in evaluating viability of the post‐trauma proximal pole of scaphoid.